Mathematical reasoning ability based on students anxiety in STAD learning with performance assessment - Zakaria, Ahmad; Amidi, Amidi (Department of Mathematics, Universitas Negeri Semarang, 2020)
Mathematical reasoning ability is very important for students in solving a problem, but the Indonesian student’s mathematical reasoning ability is still not optimal. The purpose of this research is (1) to test student’s mathematical reasoning abilities in Student Team Achievement Division (STAD) learning with Performance Assessment achieving learning completeness, (2) to describe mathematical reasoning abilities based on student anxiety in STAD learning with Performance Assessment. This research is a mixed methods research with concurrent embedded design. The population in this study were students of grade VIII Islamic Junior High School in Kendal Central Java in the 2018/2019 academic year. Random sampling technique is used as a sampling method and the subject is determined with a purposive sampling technique. The results showed that STAD learning with Performance Assessment achieved classical completeness, namely more than 75% of students who participated in STAD learning with Performance Assessment reached 70 scores. Mathematical reasoning ability of students with low anxiety described as very good in fulfilling all indicators of mathematical reasoning ability i.e. submitting guesses, doing manipulation/mathematical calculations, drawing conclusions, and giving reasons for solutions. Mathematical reasoning ability of students with medium anxiety described as fulfilling indicators submitting guesses, doing manipulation/mathematical calculations, and drawing conclusions. Description of mathematical reasoning abilities of students with high anxiety is only able to fulfill the indicator of submitting guesses. In other indicators of mathematical reasoning ability, students with high anxiety are less able to understand the problem well.